An Analytical Study on the Relationship of Land Surface Temperature with Normalized Difference Built-up Index, Urban Index, and Built-up Index - Guha Subhanil; Govil Himanshu; Srivastava Neelay (Ekológia (Bratislava), 2025)
The present study examines three urban indices: the normalized difference built-up index (NDBI), the urban index (UI), and the built-up index (BUI). It analyzes their relationship with land surface temperature (LST) using 12 Landsat 8 datasets collected during the summer season from 2013 to 2024 in Raipur, a tropical city in India. The results indicate that the mean LST of the city exceeded 40 °C in 2013, but this temperature has been moderated in subsequent years due to the implementation of ecofriendly initiatives. Among the three indices, NDBI shows the least variability. All three indices exhibit a moderate to strong positive correlation with LST, with NDBI showing the strongest correlation, followed by UI and BUI. The study suggests that environmental strategies should be maintained, with a focus on raising awareness among the public. As surface materials directly contribute to rising LST, appropriate ecological planning is essential for achieving long-term sustainability in urban thermal conditions.